Whole-Killed Blood-Stage Vaccine: Is It Worthwhile to Further Develop It to Control Malaria? - Cai, Jingjing; Chen, Suilin; Zhu, Feng; Lu, Xiao; Liu, Taiping; Xu, Wenyue (Frontiers in Microbiology, 2021)
Major challenges have been encountered regarding the development of highly efficient subunit malaria vaccines, and so whole-parasite vaccines have regained attention in recent years. The whole-killed blood-stage vaccine (WKV) is advantageous as it can be easily manufactured and efficiently induced protective immunity against a blood-stage challenge, as well as inducing cross-stage protection against both the liver and sexual-stages. However, it necessitates a high dose of parasitized red blood cell (pRBC) lysate for immunization, and this raises concerns regarding its safety and low immunogenicity. Knowledge of the major components of WKV that can induce or evade the host immune response, and the development of appropriate human-compatible adjuvants will greatly help to optimize the WKV. Therefore, we argue that the further development of the WKV is worthwhile to control and potentially eradicate malaria worldwide.